Effect of Reality Therapy and Cognitive Behavioural Therapy in Managing Social Media Addiction among Undergraduate Students of Sokoto State University - Muhammad, Sirajo; Salihu , Mukhtar Nawait; Abubakar, H. S.; Isah, Sadiq Sani (Kashere Journal of Education, 2025)
The study examined the effects of reality therapy and cognitive behaviour therapy on managing social media addictions among undergraduate students at Sokoto State University, Nigeria. Three objectives, questions and hypotheses guided the study. The study employed a quasi-experimental design involving a pre-test and post-test. The study population comprised 1271 undergraduates at level 3. Multi-stage sampling was adopted. The 50 highest scorers among the students were purposively selected as the sample of the study. Two tools were used for the research: the modified Sahin (2018) Social Media Addiction Scale-Students Form (SMAS-SF) to establish a starting point and the modified Shahnawaz and Rehman (2020) Social Media Addiction Questionnaire. To ensure face and content validity, both instruments were validated by experts at the Department of Educational Foundations, Usmanu Danfodiyo University, Sokoto. The reliability indices of 0.89 and 0.88 were obtained. The data collected for the study were analysed using inferential statistical methods. The findings of the study revealed that reality therapy is significantly effective in managing social media addiction, with a mean difference of 1.21 (t(24) = 8.69; p < .000). Secondly, the findings showed a significant effect of cognitive behaviour therapy in managing social media addiction, with a mean difference of 1.71 (t(24) = 12.76; p < .000). Thirdly, the study showed that CBT is more effective than RT in managing social media addiction with a mean difference of .360, (t (24) = 2.31; p < 0.03). It was concluded that both therapies were effective, but CBT is more effective than RT. Therefore, it was recommended, among others to use both CBT and RT in managing social media addiction among undergraduates